Empowering the community through financial planning to increase family economic independence in South Tangerang - Dini Gandini Purbaningrum; Izzatusholekha Izzatusholekha; Sunarti Sunarti (Universitas Muhammadiyah Magelang, 2024)
Rukun Tetangga 03 and 02 in Rukun Warga 01, Rempoa Village, East Ciputat District, South Tangerang City, are geographically suburban areas near Jakarta. The environment is characterized by urban villages, with most residents having completed primary education. The majority of residents fall into the middle to lower-class economic category. Facing post-pandemic economic challenges, residents often opt for cooperative loans. Limited financial knowledge leads to inadequate attention to sound financial management. In response to these challenges, this service program focuses on educating residents about family financial planning and management. The stages of the activity include problem identification, program implementation, and evaluation. The results of the educational activities demonstrate an increase in knowledge related to family financial planning and management.